Totally Umbilical Hemi-Slant Submanifolds of Kaehler Manifolds - Falleh R. Al-Solamy; Meraj Ali Khan; Siraj Uddin (Abstract and Applied Analysis)
We study totally umbilical hemi-slant submanifolds of a Kaehler manifold via curvature tensor. We prove some classification theorems for totally umbilical hemi-slant submanifolds of a Kaehler manifold and give an example.